Wiki moderators’ contributions to enhance the pedagogical implementation of Wiki - ISMAIL, NASHWA (Journal of Education Culture and Society, 2020)
Wiki has proved extensively that it is an innovative technology situated among other so-cial network applications, because it enables its users to develop web content collaboratively, thereby making it open to all online users. The pedagogical use of Wiki is still in early stages; for this reason a lot of academic research has highlighted the lack of investigation into the pe-dagogical use of Wiki as a tool for collaborative learning. This paper investigates Wiki by fo-cusing on its advantages and disadvantages for the learning process, while highlighting how Wiki moderators can contribute by embedding Wiki successfully into the learning process.